Anomaly Detection for RBAC Systems in UNIX/LINUX Environment with User Behavior - V, Shashidhar; D, Venkatesulu (International Journal of Engineering and Technology, 2018)
UNIX and LINUX are popular operating systems because of their free open source. By using RBAC model permissions are allocated based on user roles in UNIX/ LINUX environment. The RBAC model manages the privileges of the user within a system or application. However it is possible for a user to misuse his privileges that are assigned. Misuse of privileges cannot be identified by RBAC as it works based on rules. This paper suggests an anomaly detection technique to detect misuse of privileges. It keeps track of the user behavior and identifies anomalies in user behavior which helps in misuse of privileges.Â Â